Using blood pressure height index to define hypertension among secondary school adolescents in southwestern Uganda - Katamba, Godfrey; Agaba, David C.; Migisha, Richard; Namaganda, Agnes; Namayanja, Rosemary; Turyakira, Eleanor (Journal of Human Hypertension, 2020)
Hypertension is the number one risk factor for cardiovascular diseases worldwide and yet its diagnosis among adolescents, based on blood pressure percentiles which are age, height, and sex-specific, is complex. Our study intended to determine the suitability of blood pressure height index in defining adolescent hypertension among secondary school adolescents aged 12–17 years in Mbarara municipality, southwestern Uganda. Our study used data of 485 secondary school adolescents of which 173 were boys. Receiver operating characteristic curve analysis was performed to assess the performance of systolic blood pressure height index (SBPHI) and diastolic blood pressure height index (DBPHI) for screening for adolescent prehypertension and hypertension. The optimal systolic/diastolic thresholds for defining prehypertension were 0.70/0.43 mmHg/cm in boys and 0.76/0.43 in girls. The corresponding values for hypertension were 0.78/0.43 and 0.77/0.48 mmHg/cm, respectively. The negative predictive values were much higher (all ≥ 95%) for prehypertension and hypertension, while the positive predictive value was 100% for hypertension in both sexes. In conclusion, Blood pressure height index is simple and accurate for screening for prehypertension and hypertension in adolescents aged 12–17 years hence can be used for early screening of adolescents at high risk of hypertension but not its diagnosis.
Keywords: blood pressure; hypertension; adolescents; Uganda